Proximate and elementary analysis of plantain peel ash for use as fertilizer (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The study investigated the proximate and elemental composition of plantain peel ash to assess its potential as an organic-based fertilizer. Plantain peels collected from local markets were dried, burnt under controlled conditions to obtain ash, and analyzed using standard procedures. Proximate analysis revealed a high ash content (89.15%), low moisture (3.62%), and minimal organic fractions (protein, fat, and fiber), indicating a stable, mineral-rich material suitable for soil enrichment. Elemental analysis showed that potassium (35,420 mg/kg) was the dominant nutrient, followed by calcium (9,830 mg/kg), magnesium (2,740 mg/kg), and phosphorus (1,960 mg/kg). Trace amounts of iron (Fe) and zinc (Zn) were also detected. These results demonstrate that plantain peel ash contains essential macro- and micronutrients capable of improving soil structure, enhancing nutrient availability, and promoting crop growth. The high mineral and alkaline nature of the ash supports its use as an eco-friendly, low-cost soil amendment for sustainable agriculture. However, field trials are recommended to determine its agronomic efficiency and long-term effects on soil fertility.